Dietary taurine supplementation enhances metamorphosis and growth potential of Solea senegalensis larvae - Pinto, W. (2014)
The effect of dietary taurine supplementation on growth performance, metamorphosis success and amino acid metabolism of Senegalese sole (Solea senegalensis) larvae was investigated. These parameters were assessed in larvae fed control and taurine supplemented microcapsules during the pelagic phase. Subsequently, a similar evaluation was carried out in newly settled larvae fed upon Artemia, in order to verify the effect of earlier dietary taurine supplementation in larvae reared under improved feeding conditions. Results showed that dietary taurine supplementation did not affect larval growth performance and metamorphosis during the pelagic phase. However, by the end of the trial, Senegalese sole previously fed taurine supplemented microcapsules had a signiﬁcantly higher growth performance and metamorphosis completion success than larvae fed control microcapsules. These differences were likely related to the improvement of feeding conditions upon settlement, which probably helped revealing the positive effects of earlier dietary taurine supplementation on Senegalese sole performance. Additionally, Senegalese sole may have beneﬁted from taurine antioxidant properties during metamorphosis, since larval antioxidant defences may saturate at this stage. Furthermore, results from metabolic trials have shown that dietary taurine supplementation signiﬁcantly increased amino acid retention in Senegalese sole larvae when a concomitant increase of taurine body levels was found. Therefore, an increase in larval growth potential and metamorphosis success was observed under dietary taurine supplementation and these results may help understanding why dietary taurine supplementation has been reported to simultaneously increase taurine body levels and growth performance in other ﬁsh species, leading to a better comprehension on the role of taurine during ﬁsh development.